2006
DOI: 10.1159/000092343
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in <i>Helicobacter pylori</i>-Associated Idiopathic Thrombocytopenic Purpura: Eradication Reduces Platelet Activation but Seldom Improves Platelet Counts

Abstract: Introduction: It has been suggested that Helicobacter pylori eradication often increases platelet counts in patients with chronic idiopathic thrombocytopenic purpura (ITP). In addition, H. pylori has been shown to induce platelet activation (CD62p or P-selectin expression) in previous studies. We assessed the response of platelet count and CD62p expression after eradication therapy in patients with ITP and H. pylori infection. Methods and Results: We prospectively studied 15 ITP patients diagnosed with H. pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 42 publications
3
36
1
1
Order By: Relevance
“…In contrast, only three studies have been reported from the United States and Canada and they have all reported lower frequencies of both H. pylori infection and platelet count response rates following eradication treatment. [7][8][9] These data suggest that H. pylori infection may be merely an incidental observation, not excluding the diagnosis of ITP and not clinically important for management. In between these alternative interpretations are studies reporting partial platelet count responses, suggesting that H. pylori infection may contribute to the thrombocytopenia in ITP but is not the sole cause.…”
mentioning
confidence: 83%
“…In contrast, only three studies have been reported from the United States and Canada and they have all reported lower frequencies of both H. pylori infection and platelet count response rates following eradication treatment. [7][8][9] These data suggest that H. pylori infection may be merely an incidental observation, not excluding the diagnosis of ITP and not clinically important for management. In between these alternative interpretations are studies reporting partial platelet count responses, suggesting that H. pylori infection may contribute to the thrombocytopenia in ITP but is not the sole cause.…”
mentioning
confidence: 83%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][28][29][30][31][32][33][34][35] The prevalence (51%) of bacterium …”
Section: Discussionunclassified
“…A large majority of studies have suggested that alterations in lipid metabolism due to chronic tion in the atherosclerotic process 138) . On the other hand, decreased platelet activation and a reduced CD62p expression are observed after successful H. pylori eradication, which further suggests a putative link between H. pylori infection and atherosclerosis 139) . These findings support the hypothesis that the association between H. pylori infection and atherosclerosis is, at least partly, due to platelet activation and increased platelet aggregation.…”
Section: H Pylori and Other Risk Factors Modified Lipid Profilesmentioning
confidence: 93%